Increasing Equity and Achievement in Fifth Grade Mathematics: The Contribution of Content Exposure. (5th November 2013) - Ottmar, Erin R.; Konold, Timothy R.; Berry, Robert Q.; Grissmer, David W.; Cameron, Claire E.
Abstract : This study uses a large nationally representative data set (ECLS‐K) of 5, 181 students to examine the extent to which exposure to content and instructional practice contributes to mathematics achievement in fifth grade. Using hierarchical linear modeling, results suggest that more exposure to content beyond numbers and operations (i.e., geometry, algebra, measurement, and data analysis) contribute to student mathematics achievement, but there is no main effect for increased exposure on developing numbers and operations. Two significant interactions between exposure to specific content and racial composition of the classroom emerge. Specifically, as exposure to more diverse content increases, the classroom mathematics achievement gap among students in predominately Caucasian classrooms and those composed predominately of students of color appears to narrow. Findings are discussed with regard to promoting increased opportunities to learn mathematics for students in racially diverse classrooms.